2016
DOI: 10.1177/0003489416669952
|View full text |Cite
|
Sign up to set email alerts
|

Interactive iPhone/iPad App for Increased Tympanic Membrane Familiarity

Abstract: We introduce an interactive, iPhone-based smartphone application that we found to be a useful adjunct for teaching TM anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…Nevertheless, mobile apps’ interactive functions have the potential to assist users in their health care activities and improve user satisfaction [ 32 - 34 ]. A randomized controlled trial undertaken in Sweden, for example, found that an interactive health app was more effective than a noninteractive tool for improving medication adherence, lifestyle changes, and quality of life [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, mobile apps’ interactive functions have the potential to assist users in their health care activities and improve user satisfaction [ 32 - 34 ]. A randomized controlled trial undertaken in Sweden, for example, found that an interactive health app was more effective than a noninteractive tool for improving medication adherence, lifestyle changes, and quality of life [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the application developers demonstrated that medical students who used the application for eight weeks performed significantly better on pre- and post-test tympanic membrane photograph interpretation compared to controls. 7…”
Section: Buckingham Virtual Tympanummentioning
confidence: 99%
“…In this category, 5 studies could be identified focusing on different aspects [33][34][35][36][37]. Two publications dealt with apps aiming at the improvement of teaching for ENT residents.…”
Section: Studies On Apps With Regard To the Complex Of Educationmentioning
confidence: 99%
“…After one year, the participants showed a better teaching status compared to the beginning, but the paper did not make a comparison to a control group. Again without control group, another trial investigated the use of a quiz app with figures of different pathologies of the tympanic membrane [37]. After implementation of the app, a better understanding of tympanic pathologies was described compared to the situation before using the quiz app.…”
Section: Studies On Apps With Regard To the Complex Of Educationmentioning
confidence: 99%